2009
DOI: 10.1111/j.1464-410x.2008.08333.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function of patients under surveillance for bladder cancer

Abstract: surveillance scheme (demographic characteristics, a validated visual analogue scale, and validated subset of questions on sexual function and performance derived from QLQ-BLS-24). The results were compared with those from an age-and gender-matched healthy population. RESULTSThe response rate was 95% (142/150); 61% (87/142) of the respondents were sexually active in the previous 4 weeks after diagnosis, 66% (70/105) of men and 46% (17/37) of women. Although libido was not negatively affected, 54% (47/87) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…82 Recently, sexual function in NMIBC has been evaluated. 83,84 Sexual dysfunction is a prevalent problem after female radical cystectomy. The nature of the dysfunction involves multiple domains, including decreased orgasm, decreased lubrication, lack of sexual desire, and dyspareunia.…”
Section: Treatment Of Bladder Cancer In Womenmentioning
confidence: 99%
See 2 more Smart Citations
“…82 Recently, sexual function in NMIBC has been evaluated. 83,84 Sexual dysfunction is a prevalent problem after female radical cystectomy. The nature of the dysfunction involves multiple domains, including decreased orgasm, decreased lubrication, lack of sexual desire, and dyspareunia.…”
Section: Treatment Of Bladder Cancer In Womenmentioning
confidence: 99%
“…82 The treatment of NMIBC can result in sexual problems. 83,84,95 The prevalence of sexual dysfunction in patients with NMIBC is very high (54%) compared with an age-and gender-matched healthy population (20%e45%). 83 A recent study suggested that sexually active patients with NMIBC report concerns about contaminating their partners with treatment agents (23.3%).…”
Section: Treatment Of Bladder Cancer In Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of research that has been conducted on the impact of sexual function in patients with bladder cancer has focused on the treatments of MIBC by radical cystectomy (Van der Aa et al, 2009). Although less research is available regarding sexual dysfunction in patients with NMIBC, nurses should address this issue and recognize potential sexual impairments that may be directly related to treatment and surveillance.…”
Section: Nonmuscle Invasive Bladder Cancermentioning
confidence: 99%
“…After the first tumor resection all age groups of patients are monitored according to an intensive surveillance protocol that includes 3-monthly cystoscopies the first two years, followed by less frequent observations if a patient stays recurrence free. The main disadvantages of the current protocol are life-long invasive and costly cystoscopic monitoring of patients causing physical discomfort and sexual dysfunction [8]. …”
Section: Introductionmentioning
confidence: 99%